Variation in health inequalities according to measures of socioeconomic status and age - Tanya Mather; Emily Banks; Grace Joshy; Adrian Bauman; Philayrath Phongsavan; Rosemary J. Korda (Elsevier, 2014)
Abstract Objective: To examine variation in the magnitude of socioeconomic inequalities in health and age‐related variations in inequalities, according to the socioeconomic status (SES) measure used. Methods: Cross‐sectional study involving 205,709 participants in the 45 and Up Study. We used the Relative Index of Inequality (RII) to quantify health inequalities in relation to income, education and Socio‐Economic Indexes for Areas (SEIFA). The outcomes used were heart disease and self‐rated health. Analyses were stratified by age (45-64, 65-79, ≥80 years). Results: RIIs were largest for income and smallest for SEIFA; they were generally largest in the youngest age group and smallest in the oldest group. Age‐related differences in RIIs were particularly marked for income (e.g. for fair/poor health, RII=11.81, 95%CI 11.14-12.53 in the 45-64 age group and RII=2.42, 95%CI 2.10-2.78 in ≥80 group), and less marked for SEIFA (e.g. respectively, RII=2.68, 95%CI 2.53-2.84 and RII=1.32, 95%CI 1.22-1.44). Conclusions: The magnitude of socioeconomic inequality in health varies substantially according to the type of SES measure used and age. Income is the most sensitive measure. Implications: Researchers and policy makers should be aware of the extent to which SEIFA‐based estimates underestimate the magnitude of health inequality compared to individual‐level measures, especially in younger age groups.